Injury prevalence and severity in field hockey drag flickers: a retrospective cross-sectional study - Rosalie, Simon; Loh, Wei Bing; Sjurseth, Andres; Sherry, Dorianne; Iyengar, Shrikant; Wild, Catherine; Ng, Leo (Elsevier, 2015)
Loh, W. and Sjurseth, A. and Sherry, D. and Iyengar, S. and Wild, C. and Rosalie, S. and Ng, L. 2015. Injury prevalence and severity in field hockey drag flickers: a retrospective cross-sectional study, in World Confederation for Physical Therapy Congress 2015 Abstracts, May 1-4 2015. Singapore: Elsevier.